Cytological changes in cacao seed Cotyledon caused by cold treatment - Ibañez, Manuel L.; Casas, I.A.; Redshaw, E.S.; Hine Alvarado, D. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
Mature cocoa seeds (UF 613) were separated into two batches. The first batch (normal) was treated in water at 25°C for 20 minutes. The second batch (cold) was immersed in water at 4°C for the same amount of time. Microscopic α-lysis of 10-u sections from each of the treatments showed that cold affects the tannin cells found in the cotyledon. The possibility of physical changes in the cell membrane caused by cold and chemical or enzymatic lysis, initiated by the same medium, is discussed.